2009
DOI: 10.2478/s11756-009-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation and physico-chemical alteration of polyhydroxyalkanoates by a thermophilic Streptomyces sp.

Abstract: A thermophilic Streptomyces sp. capable of degrading various aliphatic polyesters was isolated from a landfill site. The isolate, Streptomyces sp. BCC23167, demonstrated rapid aerobic degradation of several polyesters, including polyhydroxyalkanoate copolymers, poly(ε-caprolactone) and polybutylene succinate at 50• C and neutral pH. The degrading activity was repressed by glucose and cellobiose, but tolerant to repression by other carbon substrates. Degradation of a commercial poly[(R)-3-hydroxybutyrate-co-3-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 35 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, natural fibres provide the more desirable glucose as a carbon source which can slow down biodegradation by glucose repression. It is still well documented that PHA degradation is repressed in the presence of glucose and cellobiose, 282 However, once these specific carbon sources are degraded in a relative area, the PHA availability will be maximized and its biodegradation will resume. A second misinterpretation is the idea that cellulose derivatives will biodegrade, which is not always correct.…”
Section: Pha-based Composite Biodegradationmentioning
confidence: 99%
“…Furthermore, natural fibres provide the more desirable glucose as a carbon source which can slow down biodegradation by glucose repression. It is still well documented that PHA degradation is repressed in the presence of glucose and cellobiose, 282 However, once these specific carbon sources are degraded in a relative area, the PHA availability will be maximized and its biodegradation will resume. A second misinterpretation is the idea that cellulose derivatives will biodegrade, which is not always correct.…”
Section: Pha-based Composite Biodegradationmentioning
confidence: 99%
“…Phithakrotchanakoon et al 46 observed that in the degradation of poly [(R) −3-hydroxybutyrate-co-3-hydroxyhexanoate] (PHBHx) by Streptomyces sp. (BCC23167) there was an increase in relative crystallinity of the film, in the early stage of degradation (<6 days), followed by a decrease in the final period.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Several microorganisms containing these enzymes have been isolated from different sources, especially from composts (Kleeberg et al 1998;Bellia et al 1999;Longieras et al 2004) because they contain diverse microorganisms (mesophiles and thermophiles) due to the changes in temperature experienced during the maturing process and the different composting materials used. Diverse polyester-degrading thermophilic actomonycetes have been isolated (Calabia and Tokiwa 2004;Hoang et al 2007;Phithakrotchanakoon et al 2009). The thermophiles Thermobifida fusca and T. alba have been isolated from composts and are potent degraders of polyesters such as aliphatic-co-aromatic polyesters (Kleeberg et al 1998;Hu et al 2008;Sinsereekul et al 2010).…”
Section: Introductionmentioning
confidence: 99%